Correction: The Untranslated Regions of Classic Swine Fever Virus RNA Trigger Apoptosis - Hsu, Wei-Li; Chen, Chung-Lun; Huang, Shi-Wei; Wu, Chia-Chen; Chen, I-Hsuan; Nadar, Muthukumar; Su, Yin-Peng; Tsai, Ching-Hsiu (PloS one, 2024)
[This corrects the article DOI: 10.1371/journal.pone.0088863.].